Pengaruh Dinamisme Lingkungan, Kemampuan Dinamis, dan Literasi Keuangan terhadap Kinerja UMKM di Kota Mojokerto - Mas Agung Maulana (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
SMEs are one of the economic contributors in East Java, and performance factors are one of the drivers of the advancement of SMEs. BPS 2016 - 2018 shows that the City of Mojokerto SMEs only contribute 0,29%, categorized as the least East Java GRDP (Gross Regional Domestic Product) contributor among other cities. This study focuses on SMEs of Mojokerto City. This research aims to find out the influence of environmental dynamism, dynamic capabilities, and financial literacy. This research is determined as quantitative causalities. The sampling method used is random sampling. 100 SMEs were being used as a sample taken from 3553 SMEs from Mojokerto City as a population. Data analysis using multiple linear regression and test instruments using SPSS 25. The result of this research is that the variable financial literacy has a positive effect on SME performance. In contrast, the variables environmental dynamism and dynamic capabilities did not affect SME performance. Mojokerto City SMEs should be aware of financial literacy rather than environmental dynamism and dynamic capabilities to increase SMEs' performance.